FPGA‐based implementation of floating point processing element for the design of efficient FIR filters - Tintu Mary John; Shanty Chacko (IET Computers & Digital Techniques)
Abstract Numerous applications based on very large scale intergration (VLSI) architecture suffer from large size components that lead to an error in the design of the filter during the stages of floating point arithmetic. Hence, it is necessary to change the architectural model that increases the design complexity and the time delay effect. The issue encountered in the VLSI architectures for finite impulse response (FIR) filter is the increased number of components, especially delay elements. For the VLSI architecture reconfigured with reduced register usage, this article provides the floating point processing element (FPPE) implementation with Cross‐Folded Shifting. The proposed FIR filter system reduces the number of components in the circuit which increases the complexity and high delay rate in the logical operation. The system has a comparatively reduced delay rate and power consumption. Hence, an efficient fast architecture based on the FPPE method is developed in this paper.